Synthesis and characterization of polyaniline-graphene quantum dot and the potential for pyrene detection using photoluminescence spectroscopy - Beygisangchin, Mahnoush (2022)
Detection of Pyrene as a toxic material is vital to possess a healthy, non-polluted and well sustainable environment since Pyrene is highly toxic and ubiquitous and is of environmental concern due to its adverse health effects. Several methods currently measure Pyrene concentration, divided into analytical and nanomaterial-based sensors/sensing. Although analytical methods are accurate and give reliable measurements, they are costly, require more extended preparation, heavy equipment, qualified operators, and a large volume of solvent in separation and extraction procedures. Moreover, nanomaterials-based sensors/sensing, particularly semiconductor quantum dots (SQDs), is ultra-sensitive, fast, and easy; however, the most significant issue related to SQDs-based probes is that there is worry regarding cadmium used in the core, which can potentially leach and further contaminate the environment after discarding the probes. Therefore, there is a need to develop a novel method which includes proper materials with a low limit of detection (LOD), cost-effective, easy, fast, simple, and user-friendly to overcome all those challenges. In this research, polyaniline-graphene quantum dot (PANI-GQD) nanocomposite films were prepared in different GQD concentrations (100 - 500) ppm by the chemical methods as a fluorescence nanomaterial, simple, sensitive, low cost and novel sensing element for the detection of Pyrene via photoluminescence (PL) spectroscopy. Before nanocomposite film preparation, PANI film was optimised using different acidic medium/dopant types (PTSA, CSA, Acetic acid, and HCl), PTSA concentrations (0.5% - 6%) selected acidic medium/dopants, and NMP concentrations (0.5% - 6%) as solvent. PANI and PANI-GQD nanocomposite films were characterized and evaluated using FT-IR, UV-vis, XRD, FE-SEM, EDS, TGA, four-point probe, and PL spectroscopy. The 1% toluene-4-sulfonic acid monohydrate and 3% N-Methyl-2-pyrrolidone doped PANI was introduced as optimized PANI film with a high conductivity value of 2.45 (Ω cm)-1, high PL intensity (excitation: 77334, emission: 37650), and low bandgap value of 2.54 (eV) due to orderly organized benzenoid and quinoid parts in its structure. In PANI-GQD nanocomposite films, the carboxylic acid groups of GQD are well-doped optimized PANI films characterized by FT-IR and UV-vis. The morphology of the PANI-GQD nanocomposites exhibited a change from nanoflakes to nonspherical with increasing GQD concentration. The PANI-GQD in 300 ppm of GQD concentration was introduced as the optimized PANI-GQD nanocomposite film with a high conductivity value of 2.28 (Ω cm)-1, high PL intensity (excitation: 231982, emission: 161435) and low bandgap value of 2.39 (eV). The PL results revealed the interaction of optimized PANI and PANI-GQD nanocomposite films with Pyrene. The LOD for Pyrene was calculated at 6.61 and 0.40 × 10-9 mol L-1 (S/N = 5) in the linear range of (0.001 - 10) × 10-9 mol L-1 based on optimized PANI and optimized PANI-GQD nanocomposite films, respectively. Furthermore, the PANI-GQD nanocomposite film showed the lowest LOD of Pyrene. The obtained LOD was comparable with WHO standards and specifications for Pyrene, which is 3.461 × 10-9 mol L-1 (0.7 µg/l) in the environment. Thus, this study proposes PANI-GQD nanocomposite film as a novel sensing element for detecting Pyrene.